Friend or foe? The impact of high‐performance work practices on workplace bullying - Salin, Denise; Notelaers, Guy (Human resource management journal, 2020)
The aim of this paper is to examine the relationship between high‐performance work practices (HPWPs) and workplace bullying and identify possible mediators. The study presents hypotheses based on two competing perspectives: a mutual gains perspective, arguing that HPWPs lead to higher perceptions of justice and less role conflict, thereby reducing the risk of bullying; and, a critical perspective, arguing that HPWPs lead to work intensification and competition among colleagues, and thereby to more bullying. A two‐wave survey (n = 209) was conducted among business professionals in Finland. The results show that HPWPs are associated with less bullying, and justice and role conflict mediated the relationship. Thus, the results provide support for the mutual gains perspective on HPWPs, challenging prevailing assumptions in the bullying literature that suggest performance‐enhancing HR practices are a risk factor. Instead, the results point to the significance of HPWPs as an important tool to prevent bullying.